Needs Analysis of Content-Differentiated Digital Teaching Materials in Learning Negotiation Text Writing - Ivana, Laili; Widyartono, Didin; Basuki, Imam Agus; Andajani, Kusubakti (Faculty of Humanities, Universitas Jenderal Soedirman, 2025)
This study aims to determine the need for content-differentiated digital teaching materials in learning to write negotiation texts. The focus of this research is to conduct a needs analysis based on the demands of the independent curriculum, previous research literature studies, classroom learning systems, and the needs of teachers and students. The grand design of the method used is qualitative method. Quantitative methods are used only to support quantitative data analysis in the needs analysis of students and teachers collected through questionnaires. The results showed that based on the needs analysis based on curriculum demands, needs based on analysis of previous research literature studies, analysis of learning needs in classrooms directly observed, and analysis of teacher and student needs, the development of differentiated digital teaching materials in learning to write negotiation texts is an urgent need in education.